More Physical Activity, More Work Engagement? : A Northern Finland Birth Cohort 1966 Study - Kiema-Junes, Heli; Saarinen, Aino; Korpelainen, Raija; Kangas, Maarit; Ala-Mursula, Leena; Pyky, Riitta; Hintsanen, Mirka (Journal of Occupational & Environmental Medicine, 2022)
Objective To examine the role of physical activity (PA) and sedentary behavior (SED) for work engagement. Methods We used data from Northern Finland Birth Cohort 1966 Study (n = 3046 to 4356) to analyze self-reported weekly leisure-time physical activity (LTPA), daily leisure-time sitting time (LTST) and work engagement. PA and SED 24-hour were also measured with accelerometer for 14 days. The data were analyzed using linear regression analyses. Results High self-reported LTPA and sports participation were associated with higher work engagement and its subdimensions. High self-reported ST was associated with lower work engagement, vigor, and absorption. Accelerometer-measured light PA was associated with higher work engagement and vigor, and accelerometermeasured steps were linked to higher vigor. Accelerometer-measured SED was associated with lower work engagement, vigor, and dedication. Conclusions Self-reported and accelerometer-measured PA and SED may play a role in people's work engagement. Peer reviewed